The Influence of Trust on Public Intention to Buy in Nunukan Regency (Case Study Lazada Online Store) - Nur Aida; Rezky Putra Supardi; Harianti Harianti (Publikasi Indonesia, 2024)
This study aims to determine if trust affects public intention to do online purchasing. The sample used for this research consisted of as many as 42 individuals who had shopped on the online marketplace (Lazada) and was collected using quota sampling. This study's data acquisition method was questionnaires. Quantitative data is employed, and SPSS 20 is utilized for data administration. The validity test, reliability test, determinant test (R2), partial test (T), and simple linear regression test are utilized as data analysis techniques. The magnitude of these variables' influence was measured using simple linear regression, the coefficient of determination, and the T-test. The straightforward linear regression test calculation yielded Y = 0.084 based on the study's findings. After comparing the t-count of 4.094 to the t-table of 2.021, it can be concluded that variable X significantly affects variable Y. The coefficient of determination is 0.18 percent, while other factors influence the remaining 0.82 percent.